The underthrusting Indian crust and its role in collision dynamics of the Eastern Himalaya in Bhutan: Insights from receiver function imaging. Issue 2 (3rd February 2017) - Singer, J.; Kissling, E.; Diehl, T.; Hetényi, G.
Abstract: Most of the convergence rate between the Indian and Eurasian plate is assumed to be absorbed along a major basal thrust beneath the Himalaya, the Main Himalayan Thrust (MHT). Deformation along this basal thrust in combination with frontal accretion results in the formation of the upper crustal fold‐thrust belt. The role of the underthrusting Indian crust and its impact on the long‐term growth of the Himalaya are only poorly understood, partly due to the lack of high‐resolution seismic images of the crust. To improve the imaging of lithospheric structures, we developed a 3‐D migration scheme for receiver functions using seismic data from the temporary GANSSER network in Bhutan. Extending the 2‐D high‐frequency ray approximation and common conversion point stacking to 3‐D including linear phase weighting and a quality assessment, we reveal significant along‐strike differences in the lithospheric structure beneath Bhutan. In western Bhutan, the Moho geometry shows an increased dip south of the Higher Himalaya reaching almost 70 km depth thereafter, whereas in eastern Bhutan the Moho is almost subhorizontal at 50 km depth across our network. The appearance of distinct listric structures beneath the MHT indicates intracrustal deformation up to crustal imbrication down to the lower crust. We propose that these variations, in the crustal thickness and in intracrustal structures, influence the upper crustal kinematics of the Bhutan Himalayan orogeny and are primarily driven by an Indian mantle‐slab northwest of Bhutan, and its absence northeast of Bhutan. Key Points: High‐resolution structural image of underthrusting Indian lithosphere and orogenic wedge enhanced by 3‐D receiver function migration Crustal‐scale listric deformation structures beneath the Main Himalayan Thrust Along‐strike variations in the collision structure across Bhutan driven by large‐scale lithosphere slab dynamics